Sanitation biomass recovery and conversion - Cookey, P. E.; Cofie, Olufunke O.; Koottatep, T.; Polprasert, C. (IWA Publishing, 2022)
Sanitation systems produce large volumes of biomass including faecal sludge, sewage, and organic waste that can be converted into valuable products such as biogas, compost, and biochar. Through physical, chemical, and biological pre-treatment and conversion methods like anaerobic digestion and pyrolysis, these wastes become sources of clean energy, fertilizers, and soil enhancers, contributing to a low-carbon circular economy. Applications are emerging across sectors. In Germany, treated sewage irrigates thousands of hectares of farmland. In Haiti and Kenya, enterprises like SOIL and Sanergy convert human waste into compost, while providing safe, affordable sanitation. These models improve environmental health and support livelihoods. Success depends on efficient value chains, quality control, and reliable service models linking waste collectors, converters, and end-users. When supported by packaging, transport, and market access, sanitation-derived products serve farmers, builders, and energy users. This approach addresses over 12 SDGs by recovering resources, reducing emissions, and closing the loop between water, energy, and food systems. With the right infrastructure and partnerships, sanitation biomass recovery offers a scalable solution to both waste management and climate resilience.